2021
DOI: 10.1371/journal.pone.0246130
|View full text |Cite
|
Sign up to set email alerts
|

“A lot of them have scary tears during childbirth…” experiences of healthcare workers who care for genitally mutilated females

Abstract: Despite concerted efforts to curb Female Genital Mutilation/Cutting (FGM/C), it is still a contributor to the high morbidity and mortality rates among females in Africa. According to available literature, the experiences of healthcare workers who care for the genitally mutilated females in Nigeria have not been described, hindering efforts towards ending this procedure through evidence-based, community-led interventions. This qualitative study described the experiences of healthcare workers caring for the geni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…From a sexual and reproductive point of view, the women interviewed described multiple complications such as dyspareunia, tearing during childbirth, anorgasmia, menstrual pain, and fertility problems, as defined by other researchers [ 16 , 31 , 39 , 41 , 43 ]. In our study, the professionals interviewed also reported vaginismus, which was also described by Berg et al [ 44 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…From a sexual and reproductive point of view, the women interviewed described multiple complications such as dyspareunia, tearing during childbirth, anorgasmia, menstrual pain, and fertility problems, as defined by other researchers [ 16 , 31 , 39 , 41 , 43 ]. In our study, the professionals interviewed also reported vaginismus, which was also described by Berg et al [ 44 ].…”
Section: Discussionmentioning
confidence: 98%
“…The physical problems that the women described in the short term after undergoing FGM were pain, dysuria, hemorrhage, anemia, and (of someone else) death [ 1 , 40 , 41 ]. In the long term, they experienced headaches and urinary tract infections [ 1 , 29 , 42 ].…”
Section: Discussionmentioning
confidence: 99%